1989
DOI: 10.1139/b89-069
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of geographic isolates of Melampsora medusae and Populus: effect of temperature

Abstract: Twelve isolates of the leaf rust pathogen Melampsora medusae Thüm., collected from six locations across the eastern U.S.A., were tested for their reaction on 18 poplar genotypes at two temperatures of incubation (16 and 26 °C). All isolates were recognized as distinct physiologic races, based on the qualitative and quantitative reaction of the isolates on the cultivars. Temperature was an important factor in determining the level and type of disease expression in most cultivar – isolate combinations. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
5

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
8
0
5
Order By: Relevance
“…diseases (DAWSON 1992;HELFER 1992;PEI et al 1993). The occurrence and development of leaf rust is affected by several abiotic factors, such as humidity and temperature (PRAKASH and HEATHER 1986;PRAKASH and THIELGES 1989). Moreover, the phytochemical quality of a host plant can affect the growth and spread of the pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…diseases (DAWSON 1992;HELFER 1992;PEI et al 1993). The occurrence and development of leaf rust is affected by several abiotic factors, such as humidity and temperature (PRAKASH and HEATHER 1986;PRAKASH and THIELGES 1989). Moreover, the phytochemical quality of a host plant can affect the growth and spread of the pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported elsewhere . For example, Prakash & Thielges (1989) found that isolates from northern locations were generally avirulent on clone ST75 (of southern origin) while most isolates of southern origin were virulent on that clone . Also, Shain (1988) reported that 10 clones originating from Stoneville, MS were more susceptible to an isolate of Mmd originating from Kentucky than to an isolate from Michigan .…”
Section: Discussionmentioning
confidence: 99%
“…Broader adaptation of southern sources of inoculum has been reported before in this system, but never quantified . For example, Prakash & Thielges (1989) and Shain (1988) observed that isolates of northern origin were avirulent on some host genotypes but virulent on others, while isolates of southern origin were virulent on all host genotypes . Jenns & Leonard's (1985) variance ratio was developed to provide an index of durability of resistance and can be loosely interpreted as the ratio of vertical to horizontal resistance .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a reasonable strategy to adopt when considering that the majority of pathogens are highly dependent on environmental conditions to cause severe damage on their host. There is evidence that rust fungi, and probably other fungal pathogens as well, can adapt to different climates and consequently generate strains that have slightly different temperature optima to infect their host (Prakash & Heather 1986;Prakash & Thielges 1989). The most damaging pathogens, however, may be difficult to locate in areas where climate is highly conducive to frequent and severe disease epidemics because they may have reduced the distribution and abundance of the host plant to very low levels (Wapshere 1985).…”
Section: Field Surveys and Climatic Matchingmentioning
confidence: 99%